Don't leave the good things in the rearview! A field experiment examining the influence of a positive work reflection intervention on taxi drivers' work behaviors - Hu, Xiaoxiao; Zhan, Yujie; Kim, Su Kyung (Irene); Jimenez, William P.; Yao, Xiang (Journal of vocational behavior, 2025)
As service jobs tend to be demanding and exhausting, it is critical to identify ways that help service employees stay positive and engage in behaviors that represent high quality customer service. Drawing upon affective events theory, this research aims to examine how a positive work reflection intervention influences service employees' work behaviors via positive affect and the role of promotion focus as a personality moderator. We used a between-subjects design to test the effects of the “three good things” positive work reflection intervention in a field experiment. Data were collected from 74 taxi drivers who were randomly assigned into either an intervention condition or a control condition. They rated their positive affect and work behaviors using daily diary surveys for 7 consecutive days, during which participants in the intervention condition completed the “three good things” exercise at the end of each workday. Results showed that participants in the intervention condition reported higher levels of morning positive affect compared to participants in the control condition, but only for those with higher levels of promotion focus. Further, the intervention indirectly increased extra-role service behavior and reduced rule breaking behavior and passive response to entitled customer demands via positive affect for individuals with higher levels of promotion focus. The intervention showed opposite effects for individuals with lower levels of promotion focus. The intervention also directly enhanced employees' active response in handling entitled customer demands. Our findings suggest that a simple exercise like the “three good things” positive work reflection intervention can significantly influence service employees' work behaviors and the importance of considering the alignment between the intervention and individual differences. •Positive work reflection intervention influenced taxi drivers' work behaviors via positive affect.•The influence of positive work reflection intervention varied across employees depending on promotion focus.•Positive work reflection intervention benefited employees high in promotion focus but hindered those low in promotion focus.•Positive work reflection intervention enhanced taxi drivers' active response to entitled customer demands.